2013
DOI: 10.1155/2013/423403
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of and Barriers to the Utilization of Health Services for Delivery in South Asia and Sub‐Saharan Africa

Abstract: The high maternal and neonatal mortality rates in South Asia and Sub-Saharan Africa can be attributed to the lack of access and utilization of health services for delivery. Data from the Demographic and Health Surveys conducted in Bangladesh, India, Pakistan, Kenya, Nigeria, and Tanzania show that more than half of the births in these countries were delivered outside a health facility. Institutional delivery was closely associated with educational level, family wealth, place of residence, and women's media exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
120
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 32 publications
20
120
2
1
Order By: Relevance
“…After controlling for confounding by adding the covariates to the logistic regression model, only one variable (having monthly income greater than 20,000FCFA) had a statistical significant association to health facility delivery utilisation. Our not finding an association with many of the socio-demographic variables is dissimilar with the study that found associations between health facility utilisation and some sociodemographic characteristics-level of education, high cost of health facility services, distance from health facility, living in rural areas [4].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…After controlling for confounding by adding the covariates to the logistic regression model, only one variable (having monthly income greater than 20,000FCFA) had a statistical significant association to health facility delivery utilisation. Our not finding an association with many of the socio-demographic variables is dissimilar with the study that found associations between health facility utilisation and some sociodemographic characteristics-level of education, high cost of health facility services, distance from health facility, living in rural areas [4].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, the factors influencing health facility delivery service utilisation in this study though varying in proportions are similar to factors influencing health facility-based deliveries as reported in studies conducted elsewhere [3,5]. In fact, some of the factors documented in this study as influencing maternal deliveries out of health facility (few or no availability of health facilities, long distances between health facilities and women's homes, sudden onset of labour, no transport to go to a health facility when in labour, bad behaviours of health workers) have also been reported in other studies elsewhere [4,9,10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Past research has suggested that such inequalities are associated with the geographical concentration of facilities in wealthier and urban areas, cultural and educational barriers to accessing facility delivery, and out-ofpocket costs incurred with transportation and user fees. 34,35,[43][44][45] Several initiatives have been launched since the 1980s to address these barriers faced by poor and rural women in low-and middle-income countries, such as increased access to institutional deliveries for poor women, home delivery by skilled attendants, training of traditional birth attendants, and vouchers for delivery in a health facility, among others. [46][47][48][49] Although some of these initiatives were successful at local or national level, they were not sufficiently scaled up to have an impact at global level.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' education has been found to be positively related to health seeking behavior for their children in general and also during pregnancy (Tey & Lai, 2013).…”
Section: Independent Variablesmentioning
confidence: 99%